2006
DOI: 10.1159/000095291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physiological and in vitroPorcine Gastric Fluid Digestion

Abstract: Background: In previous studies, the major peanut allergen Ara h 1 was digested in vitro using pepsin and porcine gastric fluid. The results suggested that in vivo gastric digestion of allergen protein can be modeled accurately by peptic hydrolysis in vitro. In the current investigation, studies were designed to follow the gastrointestinal (GI) digestion of peanut allergens under true physiological conditions. In vitro digestion with porcine gastric fluid was compared with actual physiological digestion of pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Effect of pH on Protein Binding to AC. To determine whether peanut protein adsorption onto AC is affected by pH, proteinbinding experiments were conducted at two physiologically relevant pH values: pH 7 (oral and intestinal pH) and pH 2 (gastric pH) (14). CPE was adjusted to the appropriate pH with HCl and incubated with increasing amounts of AC in separate microcentrifuge tubes at 37 °C for 2 min.…”
Section: The Significantly Larger Ara H 1 Molecule (Mw Of Ara H 1 Trimermentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of pH on Protein Binding to AC. To determine whether peanut protein adsorption onto AC is affected by pH, proteinbinding experiments were conducted at two physiologically relevant pH values: pH 7 (oral and intestinal pH) and pH 2 (gastric pH) (14). CPE was adjusted to the appropriate pH with HCl and incubated with increasing amounts of AC in separate microcentrifuge tubes at 37 °C for 2 min.…”
Section: The Significantly Larger Ara H 1 Molecule (Mw Of Ara H 1 Trimermentioning
confidence: 99%
“…The presence of peanut allergens in the insoluble roasted peanut material provides a continuous source of major allergens to the gastrointestinal mucosal immune system. A related study (14) showed that insoluble particulate material, present in both the stomach and small intestine, continuously released IgE-reactive peanut allergens as a peanut meal passed through the gastrointestinal tract. This extended release could provide a prolonged source of allergen and be largely responsible for the biphasic anaphylactic reactions observed in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, digestion of a peanut extract with pepsin did not affect the IgE‐binding properties, although substantial proteolytic breakdown was observed 32. Digestion of peanut extracts consisting of various allergens and nonallergens results in a pool of peptides that is difficult to interpret 33. Purified allergens can be used to circumvent this.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the pH value in the stomach of rats rises to 5 after allergen administration. Similarly, administration of a peanut-based meal initially neutralized the gastric pH value of piglets to approximately 7, which was subsequently acidified by HCl secretion (Kopper et al, 2006). The high pH value renders pepsin inactive.…”
Section: Foodmentioning
confidence: 99%